2021
DOI: 10.1016/j.redox.2021.101886
|View full text |Cite
|
Sign up to set email alerts
|

Tempol ameliorates polycystic ovary syndrome through attenuating intestinal oxidative stress and modulating of gut microbiota composition-serum metabolites interaction

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder, which is often accompanied by oxidative stress. Tempol, a superoxide dismutase mimetic, protects against several diseases caused by oxidative stress. However, the effect of tempol on PCOS has not been investigated. The present study demonstrated the alleviation of ovarian dysfunction and glucose tolerance in dehydroepiandrosterone (DHEA)-induced PCOS rats treated with tempol. Tempol significantly reduced the intestinal oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Taking these results into consideration, we speculated that the anti-inflammatory effect of SGD may be related to the SCFA-producing bacteria, and the mechanism needs further investigation. As reported, BAs is an important signaling molecule that regulates inflammatory response in PCOS ( Qi et al, 2019 ; Li et al, 2021 ). Our present study found that the abundance of Bacteroides , which is known as the lithocholic acid (LCA)-producing bacteria, was decreased in PCOS rats compared with normal rats, and dramatically increased after the administration of SGD.…”
Section: Discussionmentioning
confidence: 80%
“…Taking these results into consideration, we speculated that the anti-inflammatory effect of SGD may be related to the SCFA-producing bacteria, and the mechanism needs further investigation. As reported, BAs is an important signaling molecule that regulates inflammatory response in PCOS ( Qi et al, 2019 ; Li et al, 2021 ). Our present study found that the abundance of Bacteroides , which is known as the lithocholic acid (LCA)-producing bacteria, was decreased in PCOS rats compared with normal rats, and dramatically increased after the administration of SGD.…”
Section: Discussionmentioning
confidence: 80%
“…and simultaneously improved glycemia and lipid profiles [48]. A higher abundance of Ruminococcus_1 was associated with improved polycystic ovary syndrome [49]. Thus, A. muciniphila supplementation may exert beneficial changes in the intestinal microbiota structure of mother mice.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, healthy control samples were collected from healthy volunteers recruited from healthcare workers at Zhongnan Hospital of Wuhan University. Each serum sample was treated as described previously ( Li et al., 2021 ). Finally, the supernatant (≥200 μL) of serum was transferred to a new tube for quality control (QC).…”
Section: Methodsmentioning
confidence: 99%